2021
DOI: 10.1016/j.jbc.2021.100602
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical analysis of the plant-specific GIPC sphingolipids reveals multiple modes of membrane regulation

Abstract: The plant plasma membrane (PM) is an essential barrier between the cell and the external environment, controlling signal perception and transmission. It consists of an asymmetrical lipid bilayer made up of three different lipid classes: sphingolipids, sterols, and phospholipids. The glycosyl inositol phosphoryl ceramides (GIPCs), representing up to 40% of total sphingolipids, are assumed to be almost exclusively in the outer leaflet of the PM. However, their biological role and properties are poorly defined. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…Quantification of sphingolipids was performed as described in 75 , 76 . Briefly, lipids were extracted in 3 ml of propan-2-ol:hexane:water 2.75:1:1.25, incubated at 60 °C for 20 min, centrifuged and the supernatant was collected.…”
Section: Methodsmentioning
confidence: 99%
“…Quantification of sphingolipids was performed as described in 75 , 76 . Briefly, lipids were extracted in 3 ml of propan-2-ol:hexane:water 2.75:1:1.25, incubated at 60 °C for 20 min, centrifuged and the supernatant was collected.…”
Section: Methodsmentioning
confidence: 99%
“…Plant sphingolipids constitute a highly complex lipid class since they are composed of up to 9 different LCBs, 32 different fatty acids and various polar heads, which still need to be completely described in terms of exact sugar composition, kind, and stereochemistry of bounds. If several LC-MS methods based on multiple reaction monitoring mass spectrometry scan have been described to analyze the full sphingolipidome of plants [ 9 , 103 , 104 , 105 , 106 , 107 ], only relative quantification can be performed, and suitable standards for plant GIPCs are still lacking so adequate methods still need to be developed.…”
Section: Vlcfa and Sphingolipids In Plant Responses To Abiotic And Biotic Stressesmentioning
confidence: 99%
“…This particularity, easily detectable by GC-MS after silylation, facilitated sphingolipids purification and analysis in model plants [ 100 ]. The presence of VLCFA, 2-hydroxylated or not seems universal in all plant GIPCs analyzed [ 11 , 107 ]. In arabidopsis, two fatty acid 2-hydroxylases (FAH) have been described: AtFAH1, which preferentially adds a hydroxyl group to a VLCFA, and AtFAH2, which prefers 16:0 [ 114 ].…”
Section: Vlcfa and Sphingolipids In Plant Responses To Abiotic And Biotic Stressesmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies of cell cultures have consistently revealed an increase in the extent of glycosylation when compared with developed organs containing multiple cell and tissue types; enrichment of detergent-insoluble membranes from BY-2 cells revealed that GIPCs could constitute up to 60% of the lipids in this fraction. The roles of GIPCs in the functionality of these membrane domains is poorly understood, but an exciting and growing field ( Gronnier et al , 2016 ; Mamode Cassim et al ., 2019 , 2021 ).…”
Section: Expanded Insight From Other Dicotsmentioning
confidence: 99%